Pengaruh Gender, Literasi Keuangan, dan Sosial Budaya Terhadap Pengambilan Keputusan Keuangan Wirausahawan - Hana Phialsa Fauziyyah; Rohma Septiawati; Avincennia Vindy Fitriana (Jurnal Ekonomi STIEP, 2026)
Financial decision-making is a crucial factor in ensuring business sustainability. This study examine gender, financial literacy and socio-cultural factors affect financial decision-making. This study adopts a quantitative research employing PLS-SEM to examine the relationship among variables. The result denote that gender, financial literacy and socio-cultural factors have a significant effect on financial decision-making. These result suggest that financial decision-making isn’t dogged solely through financial knowledge and rational considerations, futhermore shaped through individual characteristics and socio-cultural values that influence financial behavior. This study provide to the behavorial accounting literature by consolidating individual and social in explaining financial decision-making. The findings provide implications for entrepreneurs to enhance the value of financial decision-making through enhanced financial literacy and greater awareness of gender differences and socio-cutural contexs, thereby promoting business sustainability and improve financial performance.